ESTIMATION OF IMPACT AND DIFFERENCES BETWEEN TWO GENERATION STUDENTS IN THE BIOMOTOR ABILITIES OF THE FACULTY OF PHYSICAL EDUCATION SPORTS AND HEALTH IN SKOPJE - Aleksandar Simeonov; Ratko Pavlovic (Faculty of Physical Education, Sport and Health, Skopje, 2019)
Research has been done in a sample of 94 respondents, consisted of full-time second year students at the age of 20 years with ± of 6 months at the Faculty of Physical Education Sport and Health in Skopje, divided in two groups of 47 respondents in both generations surveyed - 2013/14 and 2014/15. Respondents from both generations regularly attended athletics classes, meaning they had passed the methodology and technique of 15 athletic disciplines. To accomplish the purpose of the research, 15 athletic disciplines divided into two colloquiums, athletic pentathlon and five athletic disciplines for the exam in June were used. The practical part of the exam is the remaining 5 athletic disciplines, but also those disciplines that did not pass in both colloquiums. The results of the two generations of respondents are first processed with descriptive statistics - minimum, maximum score, central value, standard deviation and skewness and cortisone graphical representation of the results. The grades for each discipline of each respondent are processed, as well as the final assessment of the practical part.Based on the multivariate analysis on the results of both groups of entities we can conclude that both groups of respondents differ in their biomotor abilities which in this research are analyzed through motor variables which are of great importance for the successful completion of the practical part of the subject athletics. The differences between the respondents would be smaller if they paid more attention to the preparation for the practical exam.
Keywords: biomotor abilities; variables; analysis; regression; differences